THE DEVELOPMENT OF THE INDONESIAN DEFENSE INDUSTRY BY USING SYSTEMS THINKING APPROACH - Kasim Kasim; George Royke Deksino (The Republic of Indonesia Defense University, 2022)
The independence of the national defense industry is crucial in supporting the national defense system to ensure the survival and existence of the nation and state through its impact on defense capability, and national economic, and technological development. But until now there are still phenomena that show the weaknesses of the national defense industry, both in concept and practice. This study aims to explain and analyze the weaknesses of the national defense industry and propose recommendations for solutions to overcome these problems. This study uses a qualitative approach, a methodology that involves interpretation to understand and explain certain phenomena. The analytical tool used is systems thinking, which can see this phenomenon in a bigger, dynamic, and interrelated picture through a system model. The results of this study indicate that the problem we are facing includes a small defense industryâ€™s budget, lacking resources and technology, the need for raw materials, and pseudo-practices by the domestic defense industry. The proposed solution system model demonstrates how to develop the national defense industry by implementing the mandate of (Law of the Republic of Indonesia Number 16 of 2012 Concerning the Defense Industry), introducing defense product innovation through national and international defense industry exhibitions to increase investment opportunities, and implementing (Law of the Republic of Indonesia Number 11 of 2020 Concerning Job Creation) to involve private industry in the development of a strategic defense industry. Finally, the independence of the national defense industry will realize operational readiness into real operational capabilities, so that the independence of national defense will be achieved and the integrity of the sovereignty of the Republic of Indonesia will be maintained. This condition will immediately build the spirit of nationalism of Indonesian citizens.Â